Influence Of Service Quality And Facilities On The Satisfaction Of Guests Staying At The Chanti Semarang Hotel - Julius Buulolo; Krisnawati Setyaningrum (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The hospitality industry is a service sector that combines products and services, besides that the hospitality industry has other characteristics from the industry we are used to knowing where guests buy these services in the short term, this will be influenced by the physical or hotel facilities, and determine the location and quality effective service to provide satisfaction to every guest who visits or stays. This study aims to identify the effect of service quality and facilities on guest satisfaction at Chanti Hotel Semarang. From the results of SPSS calculations, a positive beta coefficient value of 1,222 is obtained with a positive value of 0,000 <0.05, so it can be concluded that the quality of service is the most dominant indicator of the variable facilities. From the results of the discussion, it can be concluded that emerged in this study, act Service quality has a positive and significant effect on guest satisfaction at Hotel Chanti Semarang. Facilities have a positive and significant effect on guest satisfaction at Hotel Chanti Semarang.